1995
DOI: 10.1038/bjc.1995.177
|View full text |Cite
|
Sign up to set email alerts
|

Expression of multidrug resistance-associated protein (MRP), MDR1 and DNA topoisomerase II in human multidrug-resistant bladder cancer cell lines

Abstract: S_ry The acquisition of the mulidrug resistance phenotype in human tumours is associated with an overexpression of the 170 kDa P-glycoprotein encoded by the multidrug resistance I (MDR1) gene, and also with a 190 kDa membrane ATP-binding protein encoded by a multidrug resistance-associated protein (MRP) gene. Human bladder cancer is a highly malignant neoplasm which is refractory to anti-cancer chemotherapy. In order to understand the hanism underying multidrug resistance in bladder cancer, we established thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…In the present study, the extent of topoisomerase I mRNA expression was similar in the multidrug-resistant sublines and the parental cell lines, which did not reflect the differences in sensitivity to CPT-1 1 and SN-38. Consistent with our finding, the expression of the topoisomerase I gene in the multidrug-resistant KK47/ADM and T24NVCR human bladder cancer sublines was similar to that in the parental cell lines, although there was an approximately threefold resistance against CPT-1 1 (Hasegawa et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the extent of topoisomerase I mRNA expression was similar in the multidrug-resistant sublines and the parental cell lines, which did not reflect the differences in sensitivity to CPT-1 1 and SN-38. Consistent with our finding, the expression of the topoisomerase I gene in the multidrug-resistant KK47/ADM and T24NVCR human bladder cancer sublines was similar to that in the parental cell lines, although there was an approximately threefold resistance against CPT-1 1 (Hasegawa et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
“…Cross-resistance against carboxylesterase-activated CPT-11 and SN-38 was observed in GLC4/ADR cells, whereas in the SW1573/Sl(MRP) cells crossresistance was not evident. Hasegawa et al (1995) have demonstrated that T24/ADM-1 and T24/ADM-2 human bladder cancer cells, both overexpressing the MRP gene, were not cross-resistant against CPT-11, whereas the cells showed cross-resistance against doxorubicin and etoposide. Thus, it is probable that CPT-1 1 is not a substrate for MRP and the cross-resistance in the GLC4/ADR subline might be related to other factors of relevance for sensitivity to CPT-l 1.…”
Section: Discussionmentioning
confidence: 99%
“…T24 cells line, established from a high grade and invasive human urinary bladder cancer patient and usually used as a model for drug sensitivity studies [21], was kindly supplied by Shanghai Institute of Cell Biology, Chinese Academy of Sciences. The cells were maintained in RPMI 1640 (GIBCO-BRL), supplemented with 5% heat-inactivated fetal calf serum (FCS), 1% Lglutamine, 1% penicillin/streptomycin solution, which contained 10,000 U/ml penicillin G and 10 mg/ml streptomycin sulfate.…”
Section: Cells Culturementioning
confidence: 99%
“…(1) reduced topo I catalytic activity (Madelaine et al, 1993;Fujimori et al, 1995;Sorensen et al, 1995), (2) decreased formation of cleavable complexes (Madelaine et al, 1993;Fujimori et al, 1995), (3) decreased expression of topo I (Eng et al, 1990;Sugimoto et al, 1990) and (4) a point mutation or rearrangement of topo I genes (Andoh et al, 1987;Fujimori et al, 1995). Reduced accumulation of TPT, due to P-glycoprotein (Pgp) overexpression, has been reported to add to resistance to topo I inhibitors as well Mattern et al, 1993;Hasegawa et al, 1995). Moreover, TPT is also a substrate for the multidrug resistance-associated protein (MRP) (Maliepaard et al, 1996).…”
mentioning
confidence: 99%